The Role of Donor Sex in Females Undergoing Repeat Kidney Transplant: Does Prior Donor Sex Matter?. Issue 8 (15th July 2022) - Craig, Stephanie; Tennankore, Karthik; Kiberd, Bryce; Worthen, George; Vinson, Amanda
Abstract : Background: Female recipients of male donor kidneys are at increased risk for graft failure because of the HY antigen effect. However, whether prior transplant with a male donor impacts subsequent transplant outcomes is unknown. Therefore, the purpose of this study was to determine whether prior male-current male donor sex is associated with an increased risk of graft failure in female recipients. Methods: We performed a cohort study of adult female recipients undergoing a second kidney transplant (2000–2017), identified using the Scientific Registry of Transplant Recipients. Using multivariable Cox models, we analyzed the risk of death-censored graft loss (DCGL) if the second transplant was from a male versus female kidney donor, conditional on donor sex at the time of the first transplant. In a secondary analysis, we stratified results by recipient age (>50 or ≤50 y) at the time of retransplant. Results: Of 5594 repeat kidney transplants, 1397 (25.0%) developed DCGL. Overall, there was no association between first and second donor sex pairing and DCGL. A prior and current female donor (FD1 FD2 ) posed a higher risk for DCGL in recipients aged >50 y at second transplant (hazard ratio, ≤0.67, confidence interval 0.46-0.98, for all other donor combinations), but posed a lower risk if aged ≤50 y at retransplant (hazard ratio, ≥1.37, confidence interval 1.04-1.80, for all other donor combinations). Conclusions: Overall, past-current donor sex pairing was not associated with DCGL in female recipients undergoing second kidney transplant; however, the risk with a past and current female donor was increased in older, and decreased in younger, female recipients at retransplant. Abstract :